Establishing turnaround potential before commencement of formal turnaround proceedings - Wesley J. Rosslyn-Smith; Marius Pretorius (The Southern African Journal of Entrepreneurship and Small Business Management, 2022)
Background: Determining the turnaround potential of a firm has plagued academia and practice. Existing failure prediction tools yield limited insight into turnaround potential and are heavily dependent on financial metrics. This framework made a valuable contribution to research in this field as it added a new perspective for decision-making purposes.